A novel proliferation synergy factor cocktail maintains proliferation and improves transfection efficiency in muscle cells and fibroblasts under low-serum conditions - Li, Jianan; Huang, Jingqi; Gao, Zeyang; He, Chunpeng; Xu, Zaiyan; Zuo, Bo (Frontiers in Cell and Developmental Biology, 2025)
Low-serum culture systems offer enhanced controllability, improved safety, and increased cost-effectiveness for applications in tissue engineering, regenerative medicine, drug screening, and cultured meat production. In this study, we developed a novel proliferation synergy factor cocktail (PSFC) consisting of IGF-1, bFGF, TGF-β, IL-6, and G-CSF under low-serum (5% FBS) conditions. This system not only sustained robust proliferation of porcine muscle satellite cells (PSCs) and porcine kidney fibroblasts (PKFs), but also exhibited broad applicability in C2C12 myoblasts and mouse skeletal muscle satellite cells (SSCs). RT-qPCR and Western blot showed that there were no significant differences in the expression levels of the proliferation marker Ki67, as well as the myogenic regulatory factors MyoG and MyHC, between the 5% FBS-PSFC culture system and the conventional serum culture system. Notably, PSFC supplementation enhanced the average transfection efficiency by 16.9% across all tested cell types. Furthermore, the 5% FBS-PSFC platform facilitated three-dimensional (3D) culture within gelatin methacryloyl (GelMA) hydrogels, enabling scalable cultured meat production while reducing serum costs by 75%. Further RNA-seq analysis revealed that the there was no significant changes in the expression of cell proliferation-related genes which may be crucial for maintaining cell proliferation of this system, while the upregulation of genes associated with membrane fluidity and endocytosis, such as ITGA3, SEMA7A, ADAM8 and AREG, may lead to the enhancement of transfection efficiency. Collectively, these findings establish a cost-effective and versatile culture platform that addresses critical challenges in cell expansion for cellular agriculture, while providing a scalable approach to enhance transfection efficiency for gene editing applications.